1996
DOI: 10.1177/014362449601700208
|View full text |Cite
|
Sign up to set email alerts
|

Aural environment survey in air-conditioned open-plan offices

Abstract: In this study, a field survey of the indoor aural environment was carried out in thirty air conditioned open-plan commercial offices in Hong Kong, with over a thousand office workers were interviewed. Subjective responses of the office workers towards their aural environments were collected using questionnaires. Physical noise measurements were performed in an attempt to establish a suitable noise criterion for aural comfort. In addition, the nature of the noise from air conditioning systems is discussed. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Unnecessary speech from general areas and neighbouring workstations were cited most frequently, followed by ringing telephones. Tang et al (1996) also reported that and colleagues were major source of noises in open plan offices. In the present study, three-item scales were adopted to assess noise disturbance.…”
Section: Noise Disturbance and Speech Privacymentioning
confidence: 93%
“…Unnecessary speech from general areas and neighbouring workstations were cited most frequently, followed by ringing telephones. Tang et al (1996) also reported that and colleagues were major source of noises in open plan offices. In the present study, three-item scales were adopted to assess noise disturbance.…”
Section: Noise Disturbance and Speech Privacymentioning
confidence: 93%
“…The questionnaire asked the office workers to rate their feeling towards the acoustical environment on an unbiased linear seven-point scale at the time the measurements were being done. The present adopted scale is similar to that used by Tang et al 5 and is shown in the Appendix. The rating obtained from the scale, which ranges from Ϫ3 to ϩ3, represents human auditory subjective rating.…”
Section: Noise Measurement and Surveymentioning
confidence: 99%
“…4 However, most people today are working in air-conditioned office buildings whose facades have relatively higher sound transmission loss so that sound transmission from the outdoors to the indoors is insignificant when compared to those generated by the building services, such as the air-conditioning system, and human activities. 5 A good acoustical environment implies good control of noise to keep its level and frequency content within the acceptable range for human beings. This issue deals with human feeling, which is very subjective in nature.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24] Ayr et al examined the effectiveness of several criteria methodologies using questionnaires and in situ office a͒ Present address: Woodruff School of Mechanical Engineering, Georgia Institute of Technology, Atlanta, GA 30332-0405. Electronic mail: eryherd@hotmail.com noise measurements.…”
Section: Previous Researchmentioning
confidence: 99%
“…22,23 The studies by Tang et al also found L Aeq to be generally well correlated with subjective auditory sensation, with other metrics performing well in certain circumstances. [18][19][20][21] Tang and Wang noted that many of their measured spectra contained some degree of tonality, but a detailed investigation of such was not the focus of their work. 21 Despite these previous studies generally supporting L Aeq , other studies have demonstrated limitations in the metric.…”
Section: Previous Researchmentioning
confidence: 99%